THE REACTION OF WATERMELON (CITRULLUS LANATUS (THUNB.) MATSUM. ET NAKAI.) TO ENVIRONMENTAL FACTORS - Sullieva Suluv Khurramovna; Zokirov Kurbonalijon Gaybullo ogli (Journals Park Publishing, 2022)
Today information teshnology is often used in the fashion industry to maintain competitiveness. There is a growing need to leverage IT, artificial intelligence teshnology and create innovations to take advantage among the fashion houses and meet consumer demand.
Keywords: thermophilic; seeds; seedlings